Design thinking Healthy Lifestyle Inspiration of the Hadith of the Prophet SAW - Wardah Azizah; Saifudin Nur (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the inspiration for hadith in a healthier lifestyle. This research method is qualitative through literature study and field studies with the hadith design thinking approach. The results and discussion of this research are the improvement of a healthy life, inspiration for the distribution of dietary applications taught by the Prophet, and maintaining a balance of food intake into the body. This study concludes that the Prophet's hadiths have inspirational messages in changing unhealthy lifestyle habits to be healthier